Efektivitas Daya Bunuh Antiseptik Benzalkonium Klorida dibandingkan Dengan Alkohol 70% - Putri, Septine Eka; Laksono, Budi; ., suhartono (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: One of the prevention of disease transmission can be done by maintaining hand hygiene, in addition to using soap, the use of hand sanitizer is an innovation to prevent disease transmission. Benzalkonium chloride is a chemical compound that can be used as a substitute for alcohol as an antiseptic.Method: This study is a true experiment with samples taken from inanimate objects in the surrounding environment using the swab method, sample identification using bacterial gram staining and effectiveness testing using the liquid dilution method to determine the MIC measured by a spectrometer and see the density of bacteria based on turbidity and solid dilution to determine MBC by looking at regrowth after 24 hours of exposureResults: The results of the study obtained MIC and MBC values in gram-positive and gram-negative bacterial samples occurred in 0.12% benzalkonium antiseptic which was marked by no bacterial growth and a decrease in turbidity after 24 hours of exposure. This is supported by statistical results stating that benzalkonium chloride has a different effect on inhibiting bacterial growth compared to 70% alcohol and from 130 bacterial test samples exposed to 70% alcohol, 14 samples (8 gram-negative bacteria and 6 gram-positive bacteria) experienced regrowth after 24 hours of exposureConclusion: This shows that 0.12% benzalkonium is more effective in inhibiting and killing gram-positive and gram-negative bacteria in the environment.